IMPACT OF SOIL MOISTURE AND COMPOSITION ON ITS PROPERTIES AND ENERGY CONSUMPTION OF TILLAGE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Two of the many factors that influence soil properties and energy consumption are soil moisture and soil composition. The correlations derived from our theoretical and experimental research allow to evaluate physical and mechanical properties of soil such as density, hardness, friction, adhesion, and to assess the draft resistance of soil tillage machines (ploughs, cultivators) depending on the value of the moisture of soil and its composition, as well as on the design parameters and operating speed of the machines, and to determine the optimum range of soil moisture when the energy capacity of tillage is the lowest.